2013
DOI: 10.1109/tim.2012.2212506
|View full text |Cite
|
Sign up to set email alerts
|

On-Road Sensor Configuration Design for Traffic Flow Prediction Using Fuzzy Neural Networks and Taguchi Method

Abstract: On-road sensors provide proactive traffic control centers with current traffic flow conditions in order to forecast the future conditions. However, the number of on-road sensors is usually huge, and not all traffic flow conditions captured by these sensors are useful for predicting future traffic flow conditions. The inclusion of all captured traffic flow conditions is an ineffective means of predicting future traffic flow. Therefore, the selection of appropriate on-road sensors, which are significantly correl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(21 citation statements)
references
References 22 publications
0
21
0
Order By: Relevance
“…The management center, which is usually deployed in a city or town, is a management entity to manage sensors and analyze the collected traffic information by neural network techniques [8]. Therefor all the on-road sensors need to communicate with the management center to transfer information or obtain some signals.…”
Section: System Architecturementioning
confidence: 99%
See 1 more Smart Citation
“…The management center, which is usually deployed in a city or town, is a management entity to manage sensors and analyze the collected traffic information by neural network techniques [8]. Therefor all the on-road sensors need to communicate with the management center to transfer information or obtain some signals.…”
Section: System Architecturementioning
confidence: 99%
“…Therefore, a typical On-Road Sensor Network (ORSN) is formed by a majority of wireless sensors communicating through radio links and certain sensors serving as data collectors and relaying collected data to a remote data center through radio or cable/fiber [7]. It boasts properties like flexible and easy deployment, two-way communication, and is distinguished from regular wireless sensor networks by its linear-like topology [8]. As illustrated in Figure 1, a typical ORSN scenario consists of a large number and variety of sensors for different ITS functions; however, as they are serving a common ITS system, they can cooperate and perform multi-hop data transmission to reduce energy consumption at individual sensor nodes [9].…”
Section: Introductionmentioning
confidence: 99%
“…This system was shown to have better functionality than traditional feed forward neural networks using back propagation learning. Further, Chan et al [21] combined a fuzzy neural network and the Taguchi method to create a traffic flow prediction model. They used the Taguchi method to set a reasonable number of on-road sensors and demonstrated that the collected information was useful.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Reference [13] proposed an approach to integrating SUMO and OMNet and [11] try to integrate the simulation of communication and traffic flow. However, most of them face problems on scalability and cannot support interactions between moving of vehicles and road information that is coming from the traffic administrator or traffic control centers [14], or from neighbourhood vehicles. This paper proposes a dynamic evolution model for urban VANETs, which is based on the similarity between the intelligent transportation and biological collective behaviors and can describe the dynamic interactive process between the collective moving behaviors of vehicles and road information.…”
Section: Introductionmentioning
confidence: 99%